Improvement of Electric Fan Manufacturing Process by Lean Six Sigma Technique - Sangkatip, Rittichai; Sriswat, Manus; Satayotin, Kosuchon; Prasong, Wattanachai (Journal of Advanced Development in Engineering and Science, 2023)
This aim of research is to apply Lean Six Sigma manufacturing system for improving of line production sample process and for increasing the process quantity to complete the customer satisfaction. Nowadays, many factories can manufacture FF-600 products up to 120 units/day but customers request 150 units/day. Therefore, a new manufacturing process using Lean Six Sigma from evaluation of time and value stream mapping (VSM) is improved in this research. The result reveals that a process of bottleneck using a manual welding process uses cycle time 360 seconds more than Takt Time which uses 176 seconds. Because the total productivity of manual frame welding is not fixed, Moreover, the new manufacturing process with adjusting Lay-Out of the manufacturing system is improved by using robot welding technology in order to increase production capacity from 120 units /day to 150 units/day that can reduce the process of bottleneck using the manual welding to balance the process and build up the standardize work. The results show that the new process can increase production capacity from 120 units/day to 145 units/day equal to 20.83%. The productivity increases from 3 units/labor hour to 8.8 units/labor hour, resulting in an increase of the productivity up to 2,943,000 bath/year.